Video Editing - Ricky Telg; Peyton Beattie (EDIS)
This 2-page publication about video editing is part of a series about developing effective video production practices. This series also covers video production, scriptwriting, and video equipment and video shot composition. Minor revision by Ricky Telg and Peyton Beattie; published by the UF/IFAS Department of Agricultural Education and Communication.